“LA NECESIDAD DE LA MEDIACIÓN COMO REQUISITO OBLIGATORIO PREVIO A LA INICIACIÓN DE UN PROCESO DE CONOCIMIENTO”. - Alvarez Torres, Pamela de los Ángeles (2025)
The present thesis work focused on the study of conflict, alternative methods for conflict resolution, focusing mainly on mediation, from its definition to its benefits, and on the importance of establishing it as a prerequisite to the approach of a court process. Subsequently, it addressed the court congestion and backlog of causes that has been increasing in our country. The methodology used was analytical, which allowed us through a detailed study, to develop the importance and validity of mediation as an alternative dispute resolution mechanism; the scientific method, which through books, scientific articles and valid documents, generates accurate knowledge for the research project; the statistical method, which helped us to verify the existing problems in our court system and the effectiveness of the agreements in mediation sessions; the comparative method guided us to elaborate a reform proposal and as research techniques we used 30 surveys to legal professionals and 5 interviews that were directed to legal professionals specialized in the subject. With respect to the field and case research, it was established that there is definitely a problem regarding the backlog of causes in our court system, therefore, by analyzing different legislations such as Argentina, Spain and Chile, we can observe that there is a need to implement mediation as a mandatory requirement prior to a trial, since its lack of application in our legislation lead to society in general to resort to the court process.